Glomus nanolumen (Glomeraceae), an arbuscular mycorrhizal fungi in Mexico - Hipólito-Piedras, Reyna P.; Méndez-Cortés, Heriberto; Ramírez-Tobías, Hugo M.; Olalde-Portugal, Víctor (Instituto de Ecología, A.C., 2024)
Background and Aims: Mexico stands out as a megadiverse country, because of its wide range of ecosystems and the diversity of plant species present, including numerous endemic species, which harbor a significant reservoir of arbuscular mycorrhizal fungi (AMF); however, a constant search effort is necessary for the identification and registration of AMF species not yet described in the national territory. The present study aimed to contribute to the knowledge of AMF in Mexico, with the record of Glomus nanolumen described from Hawaiian dunes, and in Mexico it was found in tropical deciduous forest. Methods: AMF spores were isolated from soil samples collected in tropical deciduous forest, in the state of Guanajuato, by water and sucrose centrifugation and mounted on semi-permanent slides. Taxonomic identification was performed based on the morphological characteristics of the spores, the review of the original description of the species, and online portals specialized in AMF. Key results: The species Glomus nanolumen was recorded for the first time in Mexico, associated with a tropical deciduous forest; the species is characterized by sporocarps of up to 40 ovoid, irregular or ellipsoidal spores; the structure of the spore wall is composed of two hyaline layers, turning pale yellow, the outer layer has a thickness of less than 1 µm, while the inner layer is rigid and can measure up to 10 µm thick, both layers without reaction in Melzer's reagent. Its description and taxonomic comments are presented. Conclusion: With the record of G. nanolumen, the presence of 48% of Glomus species in the country is documented, among the 55 species described worldwide. With this contribution we have a total of 163 species of AMF in Mexico.